What do Professional Forecasters actually predict? - Didier Nibbering; Richard Paap; Michel van der Wel (Tinbergen Institute, 2015)
In this paper we study what professional forecasters actually explain. We use spectral analysis and state space modeling to decompose economic time series into a trend, a business-cycle, and an irregular component. To examine which components are captured by professional forecasters we regress their forecasts on the estimated components extracted from both the spectral analysis and the state space model. For both decomposition methods we find that the Survey of Professional Forecasters can predict almost all variation in the time series due to the trend and the business-cycle, but the forecasts contain little information about the variation in the irregular component.
Keywords: C22; C53; E37; 330; Expert Forecast; Trend-Cycle Decomposition; State Space Modeling; Baxter-King Filter